Effect of Feed Rations on Semen Characteristics of Bulls at Kenya Animal Genetic Resources Center Nairobi Kenya - Ngomat, Martin Sangula; Ncene, Willian; Mushimiyamana, David; Kios, David (European Journal of Applied Sciences, 2024)
Livestock play essential part in the Kenyan economy and AI services is one of the ways to improve the making of milk and meat which are in great demand for nutritional animal protein. However, the AI conception uptake and success has remained quite low despite the potential it has to spur animal production. The study set to investigate the influence of nutrition quantity (DM7.5 Kgs (R1)-Control nutrients- DM4.4 Kgs (R2) =lower nutrition, R= high nutrients, DM9.5 Kgs (R4)=highest nutrient) of bulls on semen parameters; quantity (number of reproductive jumps, number of doses and volume) and quality(concentration, density, motility) at Kenya Animal Genetic Resources Center, Kenya. The study was an experimental in design in the Latin square framework involving 32 bulls. The volume, dosage, sperm concentration, density, and sperm motility (rate, percentage, warm, and post-thaw motility) of the semen were all measured twice a week. The difference between treatment means (SD) was calculated based on the ANOVA framework. The SPSS aided and significant level set at 0.05. The results showed that feed quantity, had a significant influence on semen characteristics. The number of doses were significantly higher in Jersey bulls (529.58268.72) than in Ayrshire (404.44188.58) and Sahiwal (430.64278.72). The volume of semen across different feed rations was not different (P>.05). The number of doses were significantly lower in bulls fed on reduced DM4.4 Kgs (R2) feed (391.53b230.16) compared to doses from bulls fed on the usual quantity DM7.5 Kgs (R1) feed (514.34a360.99). The concentration and density of semen were found significantly higher in bulls on DM5.0 (R3) and DM9.5 (R4) feeds than the reduced nutrient feed DM4.4 (R2). No difference in both concentration and density was observed between higher nutrient feeds (DM5.0 Kgs (R3) and DM9.5 Kgs (R4)) and the usual feed DM7.5 Kgs (R1). Motility (warm), Motility (diluted), Motility (post-thaw) did not differ across types of feeds. Jersey bulls proved superior in most qualitative characteristics than other breeds. It produced significantly higher concentrated semen and higher number of doses than Frisian and Sahiwal bulls.